2017
DOI: 10.22517/23447214.14281
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento microestructural de una fundición de magnesio puro con control en la temperatura de solidificación

Abstract: En este trabajo se estudió el comportamiento microestructural del magnesio (Mg) puro luego de ser sometido a un proceso de fundición realizado en un horno con control de atmósfera de fabricación propia y con control de la temperatura de solidificación. Con este trabajo se buscó determinar el cambio en la composición del Mg debido a la atmosfera protectora utilizada mediante SEM/EDS  y se estudió el cambio en la microestructura del Mg puro luego de realizar una solidificación en una lingotera a una temperatura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sergio Medina et al present information on the complexity of strengthening MgCa alloys by heat treatment. Adding Ca reduces the ignition point of Mg, however the hardness decreases when it exceeds 1.8 wt% [19,81]. Figure 3 shows the result of the third casting test of the alloy Mg -25 wt% Ca -5 wt% Zn.…”
Section: Methodsmentioning
confidence: 99%
“…Sergio Medina et al present information on the complexity of strengthening MgCa alloys by heat treatment. Adding Ca reduces the ignition point of Mg, however the hardness decreases when it exceeds 1.8 wt% [19,81]. Figure 3 shows the result of the third casting test of the alloy Mg -25 wt% Ca -5 wt% Zn.…”
Section: Methodsmentioning
confidence: 99%
“…Brar et al concluded in their research that the addition of Ca and the formation of a eutectic phase increases the resistance to corrosion and reduces the rate of degradation [18]. Additionally, Ca reduces the risks in Mg smelting, reducing the ignition point [164]. Wan et al reported that Ca does not improve the elastic limit of Mg alloys and has a beneficial effect on the compression modulus due to the presence of rigid but brittle Ca precipitates [158].…”
Section: Mechanical Properties Of Mg-zn-camentioning
confidence: 99%